Macrocyclic Azapeptide Nitriles: Structure-Based Discovery of Potent SARS-CoV-2 Main Protease Inhibitors as Antiviral Drugs - Breidenbach, Julian; Voget, Rabea; Si, Yaoyao; Hingst, Alexandra; Claff, Tobias; Sylvester, Katharina; Wolf, Valentina; Krasniqi, Vesa; Useini, Abibe; Straeter, Norbert; Ogura, Yukino; Kawaguchi, Atsushi; et al. (Journal of medicinal chemistry, 2024)
Given the crucial role of the main protease (M-pro) in the replication cycle of SARS-CoV-2, this viral cysteine protease constitutes a high-profile drug target. We investigated peptidomimetic azapeptide nitriles as auspicious, irreversibly acting inhibitors of M-pro. Our systematic approach combined an M-pro active-site scanning by combinatorially assembled azanitriles with structure-based design. Encouraged by the bioactive conformation of open-chain inhibitors, we conceptualized the novel chemotype of macrocyclic azanitriles whose binding mode was elucidated by cocrystallization. This strategy provided a favorable entropic contribution to target binding and resulted in the development of the extraordinarily potent M-pro inhibitor 84 with an IC50 value of 3.23 nM and a second-order rate constant of inactivation, k(inac)/K-i, of 448,000 M(-1)s(-1). The open-chain M-pro inhibitor 58, along with the macrocyclic compounds 83 and 84, a broad-spectrum anticoronaviral agent, demonstrated the highest antiviral activity with EC50 values in the single-digit micromolar range. Our findings are expected to promote the future development of peptidomimetic M-pro inhibitors as anti-SARS-CoV-2 agents.